Toward High‐Performance Dihydrophenazine‐Based Conjugated Microporous Polymer Cathodes for Dual‐Ion Batteries through Donor–Acceptor Structural Design - Ma, Wenyan; Luo, Lian‐Wei; Dong, Peihua; Zheng, Peiyun; Huang, Xiuhua; Zhang, Chong; Jiang, Jia‐Xing; Cao, Yong (Advanced functional materials, 2021)
Recent studies have demonstrated that dihydrophenazine (Pz) with high redox‐reversibility and high theoretical capacity is an attractive building block to construct p‐type polymer cathodes for dual‐ion batteries. However, most reported Pz‐based polymer cathodes to date still suffer from low redox activity, slow kinetics, and short cycling life. Herein, a donor–acceptor (D–A) Pz‐based conjugated microporous polymer (TzPz) cathode is constructed by integrating the electron‐donating Pz unit and the electron‐withdrawing 2,4,6‐triphenyl‐1,3,5‐triazine (Tz) unit into a polymer chain. The D–A type structure enhances the polymer conjugation degree and decreases the band gap of TzPz, facilitating electron transportation along the polymer skeletons. Therefore the TzPz cathode for dual‐ion battery shows a high reversible capacity of 192 mAh g−1 at 0.2 A g−1 with excellent rate performance (108 mAh g−1 at 30 A g−1), which is much higher than that of its counterpart polymer BzPz produced from 1,3,5‐triphenylbenzene (Bz) and Pz (148 and 44 mAh g−1 at 0.2 and 10 A g−1, respectively). More importantly, the TzPz cathode also shows a long and stable cyclability of more than 10 000 cycles. These results demonstrate that the D–A structural design is an efficient strategy for developing high‐performance polymer cathodes for dual‐ion batteries. A dihydrophenazine‐based conjugated porous polymer cathode with donor–acceptor molecular structure shows a high reversible capacity of 192 mAh g−1 at 0.2 A g−1 with excellent rate performance and ultra‐stable cyclability more than 10 000 cycles.